Various Task Allocation Simulator for Resource High-Performance based on Mobile Cloud Infrastructure - Kim, Hyun-Woo; Song, Eun-Ha (International Journal of Engineering and Technology, 2018)
Background/Objectives: We describe VTAS for efficiency of resource management, high availability in mobile cloud environment based on collaborative architecture.Methods/Statistical analysis: VTAS sets performance normalization for task allocation according to CPU, memory, and remaining battery power of mobile resources for various task processing. Visualize task allocation information and processing time when requesting work according to performance normalization.Findings: Research has been carried out in consideration of resource configuration, network connection status, number of tasks, and simulations for cloud resource management. There are insufficient studies to allocate various work processes based on mobile cloud. By assigning user task allocation criteria to simulation, task allocation for various task processing is possible.Improvements/Applications: In this paper, it is possible to apply user arbitrary task allocation criterion of limited integrated resources in mobile cloud, and more work can be processed by task allocation considering static and dynamic performance and remaining battery capacity.Â